E-commerce in Iraq - Neama, Ali Fahem; Aziz, Hassnen Hazem (Journal of College of Education, 2021)
In the rising global financial system, e-trade has increasingly come to be a vital aspect of commercial enterprise method and a sturdy impulse for financial development. One of the most enormous tendencies in commercial enterprise in latest years has been the increasing use of e-trade. It has revolutionized many marketplaces and started opportunities by no means imagined before. Organizations that are not investigating the usage of e-commerce are in a amazing hazard of locating themselves being overtaken by way of others who’re making use of this technology. Iraq is characterized as one of the very few nations inside the global which are nonetheless thus far from the actual use of inevitable offerings of e-commerce. often, Iraq suffers from some of capabilities that paintings as limitations to an effective use of e-trade in life including the lack of understanding and expertise of the gain of e-commerce, the shortage of facts and verbal exchange technologies (ICT) know-how and abilities, the risky bodily community infrastructure, protection and different privateness-associated problems similarly to problems associated with prices for the adoption of a new era. Senior leaders of the u . s . must be privy to those rising, and increasingly complicated environments of e-trade with a view to compete on a worldwide (or maybe on a nearby) level. The reason of this examine is two-fold. First, it seeks to analyze the hindrances to e-commerce adoption in Iraq. second, it seeks to suggest some tips for a hit applying of e-commerce. The paintings starts by analyzing e-commerce, its advantages, its demanding situations and market fashions of e-trade. The remainder of this paper is based as follows: in the subsequent section, an average implementation of e-trade is given, accompanied by means of the limitations to e-commerce adoption in growing countries and then limitations to its adoption in Iraq. Later, the conclusions and hints are presented and the paper is finalized with obstacle of look at and destiny paintings.